Integrasi Bursa Efek Jakarta dengan Bursa Efek di ASEAN (Setelah Penghapusan Batas Pembelian Bagi Investor Asing) - Umi Murtini; Erni Ekawati (The Indonesian Journal of Accounting Research, 2013)
The purpose of this study is to investigate the integration of BEJ with other ASEAN capital markets (Philippines, Malaysia, Thailand, and Singapore), after the abolishing of government regulation on September 1987 on the maximum limit of stock purchased by foreign investors in BEJ.On the contrary to the results of the previous researches using the data prior 1987, this study, implementing the stock index data from January 1998 to December 2001, shows that BEJ is integrated with other ASEAN capital market.  The use  of Johansen procedure of error correction model  indicates that IHSG, KLSE, PSE, SETI, and SSI are cointegrated and have different magnitude of adjusted EC-term.  This study concludes that  a comovement exists among ASEAN capital markets.